Isolation and Identification of Endophytic Cellulolytic Bacteria in Syzygium aqueum Fruit - Prasetya, Indra Adi Wira; Suryani, Elsa Mega; Ningrum, Rizka Kusuma (Biota, 2025)
Some endophytic bacteria are known to have hydrolytic activity by producing hydrolase enzymes. Endophytic bacteria can be found in plant tissue. Exploration of endophytic cellulolytic bacteria in water apple (Syzygium aqueum) fruit has not been widely carried out, so this research is the first to be conducted. This study aimed to isolate, screen, and identify endophytic bacteria from water apple fruit that could produce cellulase enzymes. The research began with bacterial isolation. Then, cellulolytic screening was carried out by inoculating the isolates into a differential medium containing cellulose, Bushnell-Haas agar (BHA). The screening results were characterized and identified through 16S rDNA gene sequence analysis. The isolation results indicated that seven bacterial isolates were screened for cellulolytic activity by cultivating them on BHA medium. The screening revealed that one isolate encode CSZA2 had cellulolytic activity with a cellulolytic index of 0.87. Biochemical characterization and molecular identification of the CSZA2 isolate showed a 99.93% similarity to the Pseudomonas putida RTI2, a bacterium known for producing cellulase enzymes. The discovery of bacterial cellulolytic activity can be developed for biomass degradation, bioethanol production, and agricultural biotechnology.